2022
DOI: 10.3389/fmolb.2022.948898
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based immunotherapy of pancreatic cancer

Abstract: Pancreatic cancer (PC) has a complex and unique tumor microenvironment (TME). Due to the physical barrier formed by the desmoplastic stroma, the delivery of drugs to the tumor tissue is limited. The TME also contributes to resistance to various immunotherapies such as cancer vaccines, chimeric antigen receptor T cell therapy and immune checkpoint inhibitors. Overcoming and/or modulating the TME is therefore one of the greatest challenges in developing new therapeutic strategies for PC. Nanoparticles have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Several reports have shown that a specific DC immature subset expands Tregs while suppressing CD8+ T cells to create an immunosuppressive microenvironment favorable for metastasis development. In addition, tumor infiltration of Treg cells plays a role in immune modulation by activating tumor-associated dendritic cells …”
Section: Immune System and Pancreatic Cancer: Current Understandingmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reports have shown that a specific DC immature subset expands Tregs while suppressing CD8+ T cells to create an immunosuppressive microenvironment favorable for metastasis development. In addition, tumor infiltration of Treg cells plays a role in immune modulation by activating tumor-associated dendritic cells …”
Section: Immune System and Pancreatic Cancer: Current Understandingmentioning
confidence: 99%
“…In addition, tumor infiltration of Treg cells plays a role in immune modulation by activating tumor-associated dendritic cells. 5 B cells, or B lymphocytes, can also regulate the outcome of immunotherapies for PDAC. 83 B cells secrete IL-35, which prompts CD8+ T lymphocytes to activate the transcription factor STAT3.…”
Section: Tumor-associated Neutrophils (Tans)mentioning
confidence: 99%
See 3 more Smart Citations